2020
DOI: 10.1111/bjh.16746
|View full text |Cite
|
Sign up to set email alerts
|

Low educational level of head of household, as a proxy for poverty, is associated with severe anaemia among children with sickle cell disease living in a low‐resource setting: evidence from the SPRING trial

Abstract: Summary Severe anaemia, defined as haemoglobin level < 6·0 g/dl, is an independent risk factor for death in individuals with sickle cell disease living in resource‐limited settings. We conducted a cross‐sectional study of 941 children with sickle cell anaemia, who had been defined as phenotype HbSS or HbSβ0 thalassaemia, aged five to 12 years, and were screened for enrollment into a large primary stroke prevention trial in Nigeria (SPRING; NCT02560935). The main aim of the study was to determine the prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A few studies conducted in the United States and Nigeria examined the effects of sociodemographic factors, parental education, and family functioning in children with SCD. [52][53][54][55] In Nigeria, socioeconomic factors, number of individuals living per room in a house, social support, and educational level of the head of the household determined the severity of anemia in children with SCD who lived in a low-resource setting. 54,55 A few other studies conducted in the United States found that the home environment and family functioning were significantly associated with cognitive development and HRQoL in children with SCD.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…A few studies conducted in the United States and Nigeria examined the effects of sociodemographic factors, parental education, and family functioning in children with SCD. [52][53][54][55] In Nigeria, socioeconomic factors, number of individuals living per room in a house, social support, and educational level of the head of the household determined the severity of anemia in children with SCD who lived in a low-resource setting. 54,55 A few other studies conducted in the United States found that the home environment and family functioning were significantly associated with cognitive development and HRQoL in children with SCD.…”
Section: Quality Of Lifementioning
confidence: 99%
“…[52][53][54][55] In Nigeria, socioeconomic factors, number of individuals living per room in a house, social support, and educational level of the head of the household determined the severity of anemia in children with SCD who lived in a low-resource setting. 54,55 A few other studies conducted in the United States found that the home environment and family functioning were significantly associated with cognitive development and HRQoL in children with SCD. 56,57 In the United States, adult patients with SCD who did not achieve higher education experienced a greater rate of ED utilization and were often unemployed compared to their peers who completed post-high school education.…”
Section: Quality Of Lifementioning
confidence: 99%
“…The clinical features of the population screened for eligibility are described elsewhere. 4,7 This descriptive study focused on specific study challenges encountered in a low-resource setting and how these challenges were addressed with a goal of building capacity for research and clinical care with ongoing quality assurance and improvement processes.…”
Section: Methodsmentioning
confidence: 99%
“…Five classical HBB haplotypes of SCD (Central African Republic, Benin, Senegal, Cameroon and Arab-Indian) have also described and are widely believed to contribute to the phenotypic variability largely through their effects on foetal haemoglobin (Hb F) levels [ 3 ]. Irrespective of the haplotype, evidence suggests that poverty influenced by lower socio-economic status could lead to adverse outcomes in the disease [ 4 , 5 ]. In the western world, more than 90% of children with SCD survive to adulthood whilst in Sub-Saharan Africa where there is the greatest burden of sickle cell anaemia estimates suggest that 50–80% of patients will die before adulthood [ 2 ].…”
Section: Introductionmentioning
confidence: 99%